Strengthening ASEAN STEAM Collaboration: Empowering Chemistry Teachers through Training on Developing STEAM-Based Assessment Instruments - Sri Yamtinah; Bakti Mulyani; Mohammad Masykuri; Maria Ulfa; Ari Syahidul Shidiq (Universitas Lambung Mangkurat, 2024)
STEAM (Science, Technology, Engineering, Art, and Mathematics) is a learning approach that encourages students to think broadly about real-world problems. However, the limited knowledge of chemistry teachers about the STEAM-based learning and assessment process causes this approach to be rarely implemented. This service aims to train teachers' skills to develop STEAM-based assessment instruments. The workshop method is used with implementation stages including preparation, implementation, evaluation, and reporting. This activity was carried out in a hybrid manner, with presentations by lecturers from Universiti Sains Malaysia and Sebelas Maret University. Participants in this activity were 68 chemistry teachers from various regions of Indonesia. Test instruments totaling 15 questions in the pretest and posttest, as well as questionnaire instruments totaling 18 questions, were used to evaluate the results of this training. As a result, participants' knowledge and skills about STEAM learning increased after the training. In addition, as many as 44% of participants are very interested in implementing STEAM in the chemistry learning process in schools. As evaluation materials, participants gave suggestions to increase the explanation time and provide more examples of STEAM-based instruments.